Review of genus Paratachycines Storozhenko, 1990 (Orthoptera: Rhaphidophoridae: Aemodogryllinae) with a new recorded species from China - Qin, Yanyan; Liu, Xianwei; Li, Kai (Zootaxa, 2019)
One species Paratachycines (Paratachycines) ussuriensis Storozhenko, 1990 from China is described and illustrated with photographs. Two other known species of Paratachycines reported by Zhang et al., (2009) from China are also mentioned. A key to four subgenera of Paratachycines and keys to species of two subgenera: Paratachycines s. str., Hemitachycines Storozhenko, 1990 worldwide are all provided.